The Effect of Learning Organization, Work Engagement, Work Motivation, and Work Stress on Innovative Work Behavior: Work Motivation and Work Stress as Mediation and Moderation - Adnan Rajak; Rusman Soleman (Universitas Mercu Buana, 2022)
Objective: This study uses a quantitative approach or post-positivism, which is looking at the influence between variables. Therefore, the main problems in this study are: Does learning organization, work engagement, work motivation, and work stress affect innovative work behavior, how is the learning organization, and work stress on work engagement, how learning organization affects work motivation, how work motivation and work engagement mediate the relationship between learning organization and Innovative Work Behavior, and the relationship between work stress and Innovative Work Behavior, and how work engagement moderates the relationship between work engagement and Innovative Work Behavior and the relationship between learning organization and Innovative Work Behavior. Methodology: The analytical model used are Structural Equation Modeling and SMART PLS (Partial Least Square) as tools for the statistical test. Data collection tools used are questionnaires and interviews, and the number of respondents was 84 civil servants. Finding: Based on the results of hypothesis testing using Smart PLS, it shows that, H1, H2, H4, and H6 are acceptable, because the t table value is greater than the calculated t value, or has an alpha (α) value smaller than 5%. Whereas H3, H5, and H7 cannot be accepted (rejected), because the value is greater than 5%.Conclusion: The results showed that: (1) Learning organization had a positive and significant effect on Innovative Work Behavior, and work motivation but had no effect on work engagement, (2) Work engagement has an effect on Innovative Work Behavior), (3) Work motivation has no effect on Innovative Work Behavior, (4) Work stress has a positive and significant effect on Innovative Work Behavior but has no effect on work engagement, (5) Work motivation fully mediates the relationship between learning organization and Innovative Work Behavior, (6) Work engagement fully mediates the relationship/influence of learning organization and work stress on Innovative Work Behavior, and (7) Work motivation does not moderate the relationship or influence of learning organization and work engagement on Innovative Work Behavior.